1987
DOI: 10.4319/lo.1987.32.3.0723
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish grazing on nutrient release and succession of primary producers1

Abstract: Abstract-Macrophytes(Anacharis canadensis) growing in aquaria were eliminated by the grazing activity of the omnivorous rudd (Scardinius erythrophthalmus). The phosphorus content in both the water column and periphyton was greater in those aquaria that contained fish. Grazing activity of rudd caused 33P0,3-that was injected into the sediment and taken up by A. canadensis through their roots to be released into the water phase. In a pond experiment, grazing rudd reduced the biomass ofA. canadensis, which in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
3

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 16 publications
0
24
3
Order By: Relevance
“…Lemna trisulca is consumed frequently, as it is freely floating, small-sized and the dominant submersed species among the stands of emergent macrophytes . When feeding on macrophytes, cyprinid fish can accelerate eutrophication by releasing nutrients incorporated from the sediment by macrophytes (Hansson et al ., 1987) . The roach do not recycle nutrients from the sediment when they feed on freely-floating species like lemnids, but they can reduce the ability of macrophytes to compete for nutrients with algae by reducing their biomass and promote the succession from macrophytes to phytoplankton .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lemna trisulca is consumed frequently, as it is freely floating, small-sized and the dominant submersed species among the stands of emergent macrophytes . When feeding on macrophytes, cyprinid fish can accelerate eutrophication by releasing nutrients incorporated from the sediment by macrophytes (Hansson et al ., 1987) . The roach do not recycle nutrients from the sediment when they feed on freely-floating species like lemnids, but they can reduce the ability of macrophytes to compete for nutrients with algae by reducing their biomass and promote the succession from macrophytes to phytoplankton .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of cyprinid fish on water quality in lakes has been shown in several studies (Andersson et al, 1978 ;Henrikson et al ., 1980 ;Hessen & Nilssen, 1986 ;Tatrai & Istvanovics, 1986 ;Hansson et al, 1987 ;Brabrand et al, 1990 ;Horppila & Kairesalo, 1990 . The fish can affect water quality by consuming zooplankton, by their excretory products and by releasing nutrients from the sediments by their feeding activities .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lodge et al (1998) suggested that macrophyte herbivory may tip aquatic systems from a clear to a turbid state. Despite several studies showing that herbivores, such as birds (van Donk 1998), fish (Hansson et al 1987), and crayfish (Lodge et al 1998) feed on aquatic macrophytes, such herbivores have not been shown to induce shifts in states in freshwater systems. Our study, however, demonstrates how feeding by an invertebrate herbivore can mediate a shift from clear water and macrophyte dominance to turbid water and phytoplankton dominance by making biologically fixed nutrients from macrophyte plants available for planktonic algae.…”
mentioning
confidence: 99%
“…As a result of this overestimation, fish excretion could be a more important nutrient source than estimated in our study. However, fish-derived nutrient load seems to be unlikely to have a relevant effect on nutrient dynamics of lake ecosystems, contrarily to previous evaluations (Hansson et al, 1987).…”
Section: Is Fish Presence a Significant Element Altering Nutrient Cycmentioning
confidence: 81%